Heaven's Gift : Peter Noever, Sepp Müller, Michael Embacher : Contemporary Art Tower : The Arenbergpark Flak Tower Wien. - David, Catherine; Groys, Boris; Krens, Thomas; Virilio, Paul; Woods, Lebbeus; MAK (Österreichisches Museum für angewandte Kunst/Gegenwartskunst), Wien; MAK - Center for Art and Architecture, Los Angeles (Ostfildern-Ruit : Hatje Cantz Verlag, 2000)
With their Contemporary Art Tower project, the planning team Peter Noever, Sepp Müller, Michael Embacher have developed a radically new programmatic strategy that comes up to the complex requirements of today's artistic productions. CAT suggests to adapt an antiaircraft tower in Vienna's Arenbergpark built in 1942 and '43, a memorial to never forget the Nazi regime and its war, to an international center for contemporary art. After intense study of the CAT project, Jenny Holzer (New York) and James Turrell (Flagstaff/Arizona) have worked out artistic interventions for the site. The CAT project is presented under the title Heaven's Gift - an exhibition shown at Max Protetch Gallery in New York for the first time.
biog. (flaptekst)
Engels
Heaven's gift : A New Programmatic Strategy for the Presentation of Contemporary Art, Max Protetch Gallery, New York from June 30 to July 28, 2000
boek
Keywords: Noever, Peter; Müller, Sepp; Embacher, Michael; Holzer, Jenny; Turrell, James; Wien